2017
DOI: 10.1186/s12906-017-2040-5
|View full text |Cite
|
Sign up to set email alerts
|

Adding Chinese herbal medicine to conventional therapy brings cognitive benefits to patients with Alzheimer’s disease: a retrospective analysis

Abstract: BackgroundConventional therapy (CT) such as donepezil and memantine are well-known short-term treatments for the symptoms of Alzheimer’s disease (AD). The efficacy of them, however, drops below baseline level after 9 months. In China, herbal therapy as a complementary therapy is very popular. Should conventional therapy combined with herbal therapy (CT + H) make add-on benefit?MethodsIn this retrospective cohort study, 344 outpatients diagnosed as probable dementia due to AD were collected, with the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Additionally, the current drug design of AD has shifted from a single-targeted approach (mainly centered on amyloid) to the multi-target one, and from treatment at the later stage of disease to the prevention strategy at the early stage of development. Shi et al conducted experiments on AD patients treated with conventional therapy and conventional therapy combined with herbal therapy (CT + H) in a clinical setting [125]. MMSE was performed every 3 months for cognitive function, and the longest follow up was 24 months.…”
Section: Experimental Periodmentioning
confidence: 99%
“…Additionally, the current drug design of AD has shifted from a single-targeted approach (mainly centered on amyloid) to the multi-target one, and from treatment at the later stage of disease to the prevention strategy at the early stage of development. Shi et al conducted experiments on AD patients treated with conventional therapy and conventional therapy combined with herbal therapy (CT + H) in a clinical setting [125]. MMSE was performed every 3 months for cognitive function, and the longest follow up was 24 months.…”
Section: Experimental Periodmentioning
confidence: 99%
“…The authors report that one of the most notable impacts of the formulae is inhibition of Aβ accumulation. They particularly highlight that a treatment regimen comprising a herbal formula named GRAPE (encompassing Panax ginseng , Rehmannia glutinosa , Acorus tatarinowii , Polygala tenuifolia , Epimedium brevicornu, Cornus officinalis, Cistanche deserticola, Curcuma aromatica, Salvia miltiorrhiza, Angelica sinensis, Gastrodia elata, Coptis chinensis ) and AD approved drugs donepezil and/or memantine was more beneficial on cognitive function than treatment with conventional drugs alone [91]. Additional studies showed that Bushen Tiansui decoction (comprising Epimedium brevicornum Maxim , Polygonum multiflorum Thunb , Chinemys reevesii, Fossilia Ossis Mastodi, Polygala, Acorus tatarinowii ) and triterpenoid saponins of Xanthoceras sorbifolia Bunge decreased hippocampal damage and cognitive deficits induced by Aβ aggregation [92, 93].…”
Section: Traditional Oriental Medicines May Be Useful For Slowing Dowmentioning
confidence: 99%
“…One study proposes that a combination of conventional therapy drugs and Chinese herbal therapy could be the solution to AD. 344 patients diagnosed with AD were treated either with conventional therapy drugs or a combination of conventional therapy drugs and Chinese herbal therapy [ 39 ]. The study was conducted over a period of 24 months, and at the beginning of the study, most patients had mild or moderate AD.…”
Section: Traditional Chinese Medicine (Tcm) and Network Pharmacolomentioning
confidence: 99%
“…The study was conducted over a period of 24 months, and at the beginning of the study, most patients had mild or moderate AD. After 18 months, based on results of the Mini-Mental State Examination (MMSE), patients treated with a combination of conventional therapy drugs and Chinese herbal therapy scored 1.76 points higher than patients treated with only conventional therapy drugs, and after 24 months, patients treated with the combination scored 2.52 points higher than patients treated with only conventional therapy [ 39 ]. This study presents an argument for a multifaceted approach to AD treatment, and a combination of conventional single target therapy and TCM herbal therapy.…”
Section: Traditional Chinese Medicine (Tcm) and Network Pharmacolomentioning
confidence: 99%